1989
DOI: 10.1113/jphysiol.1989.sp017550
|View full text |Cite
|
Sign up to set email alerts
|

The inactivating K+ current in GH3 pituitary cells and its modification by chemical reagents.

Abstract: SUMMARY1. Whole-cell and single-channel recording techniques were applied to the study of the permeability and gating of inactivating K+ channels from clonal pituitary cells.2. The cation selectivity sequence (measured from reversal potentials) for the channels underlying the inactivating K+ current was TlV > K+ > Rb+ > NH4+. The conductance sequence (determined from current amplitudes) was K+ = Tl > Rb+ > NH4t3. The inactivating current (IK(i)) which was blocked by 4-aminopyridine (4-AP), activated at voltage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
59
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 56 publications
(71 reference statements)
15
59
0
Order By: Relevance
“…Except in immunoblot experiments, amylin and bovine serum albumin (0.5 mg/ml) were dissolved into the external recording solution immediately prior to application to single cells via a U-tube (11). Amylin can precipitate from solution and adheres avidly to both plastics and glass, thus actual concentrations of the delivered peptide are likely lower than those reported.…”
Section: Methodsmentioning
confidence: 99%
“…Except in immunoblot experiments, amylin and bovine serum albumin (0.5 mg/ml) were dissolved into the external recording solution immediately prior to application to single cells via a U-tube (11). Amylin can precipitate from solution and adheres avidly to both plastics and glass, thus actual concentrations of the delivered peptide are likely lower than those reported.…”
Section: Methodsmentioning
confidence: 99%
“…Its effects on ionic channels have not been widely explored, but it is known that similar agents are capable of slowing down the inactivation of the Na¤ current (Ulbricht, 1990). We chose IAA because it did not affect the inactivation properties of K¤ currents in the experiments performed by Oxford & Wagoner (1989). When added to the pipette solution, we found that IAA increased the INa,p in neocortical neurones, without inducing a large shift in the voltage dependence of current activation.…”
Section: Effects Of Other Agents Acting On Na¤ Current Inactivationmentioning
confidence: 99%
“…Under such conditions, two types of K+ current can be observed in GH, cells: first, a voltage-dependent inactivating current sensitive to 4-aminopyridine (4-AP, Dubinsky and Oxford, 1984;Oxford and Wagoner, 1989) and second, a noninactivating, voltage-activated current that is at least partially blocked by 5 mM TEA (Oxford and Wagoner, 1989). Some evidence supports the view that this current reflects Ca2+-activated K+ current activated by voltage in the absence of Ca*+ (Oxford and Wagoner, 1989). However, at present, some contribution of a delayed-rectifier type of K+ channel cannot be excluded.…”
Section: Concentration Dependence Of Blockade Of Ca2+ Current By Halomentioning
confidence: 99%